2016
DOI: 10.1111/rec.12344
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transformation rates are affected by cover soil type but not coarse woody debris application in reclaimed oil sands soils

Abstract: Forest floor mineral soil mix (FMM) and peat mineral soil mix (PMM) are cover soils commonly used for reclamation of open-pit oil sands mining disturbed land in northern Alberta, Canada; coarse woody debris (CWD) is another source of organic matter for land reclamation. We investigated net nitrogen (N) transformation rates in FMM and PMM cover soils near and away from CWD 4-6 years after oil sands reclamation. Monthly net nitrification and N mineralization rates varied over time; however, mean rates across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Plant Root Simulator (PRS) probes (ion exchange resin membranes in a rigid plastic housing that allows for relatively easy insertion into the soil profile) have become a mainstream tool for characterizing soil nutrient supply in the Athabasca Oil Sands Region due to the simplicity of installation in the field, having a quantifiable surface area, providing results integration over time (though not a simple linear integration), and the low cost associated with obtaining a relatively complete spectrum of nutrients present in the soil profile. The majority of boreal forest studies implementing PRS probes for assessing nutrient supply rates have occurred in upland forests and in post‐oil sand mining terrestrial substrate capping studies, and PRS incubation periods typically exceed 3 weeks (Howell, Das Gupta, Pinno, & MacKenzie, ; Kwak, Chang, Naeth, & Schaaf, ). Fewer studies have implemented PRS probes to assess nutrient supply rates in undisturbed boreal fens or reclaimed wetlands (e.g., Nikanotee Fen—Suncor and Sandhill Fen—Syncrude Canada, Ltd.; Nwaishi et al, ; Wood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant Root Simulator (PRS) probes (ion exchange resin membranes in a rigid plastic housing that allows for relatively easy insertion into the soil profile) have become a mainstream tool for characterizing soil nutrient supply in the Athabasca Oil Sands Region due to the simplicity of installation in the field, having a quantifiable surface area, providing results integration over time (though not a simple linear integration), and the low cost associated with obtaining a relatively complete spectrum of nutrients present in the soil profile. The majority of boreal forest studies implementing PRS probes for assessing nutrient supply rates have occurred in upland forests and in post‐oil sand mining terrestrial substrate capping studies, and PRS incubation periods typically exceed 3 weeks (Howell, Das Gupta, Pinno, & MacKenzie, ; Kwak, Chang, Naeth, & Schaaf, ). Fewer studies have implemented PRS probes to assess nutrient supply rates in undisturbed boreal fens or reclaimed wetlands (e.g., Nikanotee Fen—Suncor and Sandhill Fen—Syncrude Canada, Ltd.; Nwaishi et al, ; Wood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of using PRS probes over conventional soil sampling approaches (i.e., soil nutrient extractions) include reduced soil disturbance during installation/removal, providing a consistent quantifiable surface area, and allowing for nutrient supply integrations over time (Skogley & Dobermann, 1996). Most studies utilizing PRS probes have carried out incubations that exceed 2-week periods (Howell, Das Gupta, Pinno, & MacKenzie, 2016;Kwak, Chang, Naeth, & Schaaf, 2016;Wood et al, 2016). In an extreme-rich fen (mean porewater electrical conductivity [EC] of 270 μS/cm), however, Hartsock and Bremer (2018) found that most nutrients were close to equilibrium on PRS probe membranes within 24 hr and were constant thereafter except for the monovalent cation potassium (which declined between 2 and 16 days after burial due to displacement by divalent cations).…”
mentioning
confidence: 99%
“…Bars indicate standard error, and asterisks represent p values generated from post hoc analysis (Tukey's test) that compares subset species across soil treatments (***p < 0.001, **p < 0.01, *p < 0.05) treatments was the inorganic nitrogen availability, with PMM having the lowest, FFMM having the highest, and fertilization increasing availability for all soils. These differences in nutrient availability between reclamation cover soils have been found in other studies (Duan et al 2015;Kwak et al 2016;Pinno et al 2013). Outside of a greenhouse setting, both M. perforata and G. boreale are sensitive to reduced inorganic nitrogen availabilities (Kim et al 2006;Staples et al 1999).…”
Section: Discussionmentioning
confidence: 53%
“…The difference in nutrient profiles for these two reclamation soils has important implications for plant growth and development. FFMM has lower C:N ratios with higher nitrogen mineralization and inorganic nitrogen supply rates compared to PMM, resulting in greater vegetation cover and plant growth on the FFMM (Kwak et al 2016). Despite FFMM's greater inorganic nitrogen availability and initial plant growth, it cannot be used in place of PMM consistently because there is a limited availability within the region.…”
Section: Introductionmentioning
confidence: 99%